Upaya Meningkatkan Ketrampilan Menyimak Dongeng Melalui Model Story Telling Dengan Media Kartu Bergambar - Mela Amanda, Yosi Anggaraeyni, Safrida Napitupulu, Desi Eka Syafitri, Fitanty, Halimatus Syadiah, (Lembaga Penelitian dan Pengabdian Masyarakat, 2023)
The aim of this research is to improve the skills of listening to fairy tales through a story telling model using picture cards for class II students at SDN 104247 Tanjung Mulia. The method used in this research is a classroom action research method using 2 cycles with different results. The subjects of this research were all class II students at SDN 104247 Tanjung Mulia, totaling 22 students. The instruments used to obtain data were observation sheets and field notes. The data analysis technique used is quantitative and qualitative data obtained from observations of student activities and teacher skills in learning Indonesian using the story telling model with picture cards as media. The research results showed that there was an increase from cycle I of 71.02% in the good category and cycle II of 90.33% in the very good category.